Maids, nannies and their work – views of Nigerian female employers - Habib, Nu’uman Mohammed (Advances in Social Sciences Research Journal, 2019)
This paper explores the views of employers of maids and nannies – girls aged 8 to 16 – who help look after their children and household, thus enabling them to pursue education and career. The women employers are privileged, high status occupants, while the maids and nannies, who are poor rural, took up the employment to help put food on the table for their families. However, taking up such jobs not only exposes the child maids and nannies to several hazards, it denies them the chance for education. In interviews with the employers, the paper found that without the services of the maids and nurses, many of them would have been severely constrained to pursue higher education or career. In other words, as long as the conditions that propels young children to seek jobs as domestic workers persist, and for as long as there are no alternatives for the privileged urban-based woman, child domestic work will continue.